Diaspora Mobilizations in the Egyptian (Post)Revolutionary Process: Comparing Transnational Political Participation in Paris and Vienna. Issue 3 (2nd July 2016) - Müller-Funk, Lea
ABSTRACT: This article sheds light on the patterns of diaspora mobilization in different settings by placing it in the transnational realm. The article does so by comparing Egyptian activism during the revolution and transformation period (2011–2013) in two European capitals, Paris and Vienna. I argue that different features—emigrant policies of the sending country, integration policies of the receiving country, and characteristics of the migrant group—influence the degree and form of diaspora mobilization.